Exploration of Mechanisms of Joint Deterioration in Concrete Pavements regarding Interfacial Transition Zone - Xin Wang; Jiake Zhang; Xuhao Wang; Peter Taylor; Kejin Wang; Xinjian Sun (Advances in Civil Engineering)
As a common issue for cold weather regions, premature deterioration of concrete at joints has been reported in many states. In this paper, the mechanisms of joint deterioration were investigated, and then, experimental investigations were conducted to further verify some of the mechanisms. It was found that freeze-thaw (F-T) damage and salt crystallization are not enough to cause the observed deterioration, but the deterioration near the interfacial transition zone (ITZ) may be the cause of some of the observed phenomena. In the experimental work, samples were tested at 40°F in salt solutions to observe the deterioration in the ITZ using the scanning electron microscope (SEM). Concrete tested in MgCl2 solution indicated distress in ITZ under SEM. It was found that ITZ may act as a shortcut for ion transfer to surrounding concrete near the joints and may also be the weak point for cracking due to expansion of the paste.